94.2k views
4 votes
Solve for x.

a) 9
9^(3x+4) =
27^(4x+3)
b)
4^(3x) =
2^(x+1)

(include steps pleez)

User Murena
by
6.2k points

1 Answer

4 votes

Answer:

Question a)


9^(3x+4)=27^(4x+3)


x=-0.166

Question b)


4^(3x)=2^(x+1)


x=0.2

Explanation:

Question a)

Given the expression


9^(3x+4)=27^(4x+3)

Taking log on both sides


log\left(9^(3x+4)\right)=log\left(27^(4x+3)\right)


\left(3x+4\right)\cdot \left(log\left(9\right)\right)\:=\left(4x+3\right)\cdot \left(log\left(27\right)\right)


3x+4=\left((log\left(27\right))/(log\left(9\right))\right)\cdot \left(4x+3\right)


3x+4=1.5* \left(4x+3\right)


3x+4=6x+4.5


3x=6x+0.5


(-3x)/(-3)=(0.5)/(-3)


x=-0.166

Therefore, the value of x:


x=-0.166

Question b)

Similarly, we can solve the 'b' expression

Given the expression


4^(3x)=2^(x+1)

Taking log on both sides


log\left(4^(3x)\right)=log\left(2^(x+1)\right)


3x\cdot \left(log\left(4\right)\right)=\left(x+1\right)\cdot \left(log\left(2\right)\right)


3x=\left((log\left(2\right))/(log\left(4\right))\right)\cdot \left(x+1\right)


3x=0.5* \left(x+1\right)


3x=0.5x+0.5


2.5x=0.5

Divide both sides by 2.5


(2.5x)/(2.5)=(0.5)/(2.5)


x=0.2

Therefore, the value of x = 0.2

User Bananeweizen
by
6.7k points